Dinamika Perkembangan Kebudayaan di Persia dan Mesir Kuno - Berliana Fatihatuz Fiizha; Mohammad Robby M; Rizky Apria Bakti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
The ancient persians and egyptians were known as the originators and beginnings of modern civilization today in the world, from these two civilizations close to the great rivers. Early in its civilization, Persia developed through warfare and conquest of other areas without war powers and fertile areas the expansion of territory was the only way to make progress. The education of the era was still one of harsh military education and extremely high discipline, because the persians were the main military force to conquer the land rather than technological or scientific advancement. The ancient egyptians are enjoyed a greater cultural and educational culture than the persians because military forces of both land and sea are rather popular. The ancient egyptians were extremely wealthy, supported by natural resources, because they lived along the Nile's regular flood course and caused the region around the river to become fertile and suitable for cultivation.